Caribbean Report 10-02-1993 - Ransome, Debbie (anchor); Islam, Shada (correspondent); Davalos, Luis (interviewee); Allen, Gary (correspondent); Small, Hugh (interviewee); Blaize, Hayden (interviewee); Thompson, Pat (interviewee); Baptiste, Sandra (correspondent); Johnson, Andy (correspndent) (The British Broadcasting Corporation, 1993)
The European Farm counsel remains deadlocked over the ratification of a new banana import regime agreed to in December but the decision has been receded. And, opposition to the plan is being led by Germany and supported by Belgium and Holland – correspondent Debbie Ransome and Shada Islam in an interview with Luis Davalos reports. In an interview with correspondent Gary Allen, Jamaica’s Finance Minister - Hugh Small points an accusing finger at opposition leader Edward Philip George Seaga after uncovering the Bank of Jamaica’s (the country’s Central Bank) failure to alert the bank that its agents have been abusing the foreign exchange system. The nature of the accusation also points to severe shortcomings in the banks monitoring system. After a private sector conference in Georgetown, Guyana an agreement was made for a more structured consultation between the region’s social partners. And a package of financial and technical assistance aimed at measures to resuscitate the region’s manufacturing sector is to be developed by June. Pat Thompson CDB - Executive Director, Caribbean Association of Industry and Commerce is interviewed by correspondent Sandra Baptiste. The Trinidad and Tobago government has issued press advertisements on behalf of the country’s Finance Ministry explaining why it can’t afford to trade union’s demands correspondents Sandra Baptiste and Andy Johnson report. Criticism of a new UNs agreement with Haiti’s de facto government came today from Paul Dejean - a prominent supporter of exiled Haitian President Jean Bertrand Aristide. Paul Dejean accused UN envoy Dante Caputo of betraying Father Aristide who had originally requested the idea of an“Observer Force.” He said that the agreement showed President Bill Clinton was leaning more towards the Bush administration position and thus reneging on his election promises.
Headlines with anchor Debbie Ransome (00:00 - 00:35).
1. The European Farm counsel remains deadlocked over the ratification of a new banana import regime agreed to in December but the decision has been receded (00:34-04:33).
2. In an interview with correspondent Gary Allen, Jamaica’s Finance Minister - Hugh Small points an accusing finger at opposition leader Edward Philip George Seaga, after uncovering the Bank of Jamaica’s (the country’s Central Bank) failure to alert the bank that its agents have been abusing the foreign exchange system (04:34-07:01).
3. After a private sector conference in Georgetown, Guyana an agreement was made for a more structured consultation between the regions’s social partners (07:02-10:43).
Keywords: Jamaica--Corrupt practices--Politics and government.; Jamaica--Commerce.; Foreign exchange--Law and legislation--Jamaica.; Foreign exchange rates--Jamaica.; Manufacturing industries--Caribbean Area.; Commercial policy—Commerce--Caribbean Area.; Caribbean Community--Commerce.; Labor disputes-Trinidad and Tobago-History-20th century.; Labor movement-Trinidad and Tobago.; Government and politics—Trinidad and Tobago.; Haiti--Foreign relations--United States.; United Nations--Haiti.; Haiti—Politics and government.; Haiti—Social conditions.